On-Farm Management of Vitellaria paradoxa C. F. Gaertn. in Amuria District, Eastern Uganda - Paul Okiror; Jacob Godfrey Agea; Clement Akais Okia; John Bosco Lamoris Okullo (International Journal of Forestry Research)
The population of shea butter tree (Vitellaria paradoxa C. F. Gaertn.)—a priority tree with enormous economic and cultural values to the parkland communities in Uganda, is rapidly declining due to rapid human population growth, increasing land fragmentation, and high demand for woodfuel especially charcoal. Reversing this trend will depend on the rural community involvement in the planting, facilitating natural regeneration, and tending of shea trees on farm. As such a survey was conducted in Amuria district, eastern Uganda, to assess local strategies and constraints to on-farm management of shea trees, and document socio-demographic factors influencing the on-farm conservation. About 93% of the households protected naturally regenerated V. paradoxa trees mainly on farms. V. paradoxa was mostly propagated through coppices and seedlings. Although insecure land tenure, insecurity, pests, disease, and shortage of planting materials were reported as major hindrances, farmsize, family size, and gender significantly (P≤0.05) influenced people’s willingness to conserve V. paradoxa. Byelaws and policies on shea conservation need to be properly enforced, and further propagation research is required especially towards shortening the juvenile period of V. paradoxa so that more farmers can start propagating the tree other than relying on its natural regeneration.